Four-lepton production in gluon fusion at NLO matched to parton showers - Simone Alioli; Silvia Ferrario Ravasio; Jonas M. Lindert; Raoul Röntsch (European Physical Journal C: Particles and Fields, 2021)
Abstract We present a calculation of the next-to-leading order (NLO) QCD corrections to gluon-induced electroweak gauge boson pair production, $$gg → ZZ$$ g g → Z Z and $$gg → W^+W^-$$ g g → W + W - , matched to the PYTHIA 8 parton shower in the POWHEG approach. The calculation consistently incorporates the continuum background, the Higgs-mediated $$gg→ H^* → VV$$ g g → H ∗ → V V process, and their interference. We consider leptonic decay modes of the vector bosons and retain offshell and non-resonant contributions. The processes considered are loop-induced at leading order and thus contain two-loop virtual contributions as well as loop-squared real contributions. Parton-shower effects are found to be marginal in inclusive observables and quite sizeable in observables that are exclusive in additional jet radiation. The Monte Carlo generator presented here allows for realistic experimental effects to be incorporated in state-of-the-art precision analyses of diboson production and of the Higgs boson in the offshell regime.